2021
DOI: 10.1186/s12885-021-08028-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pegylated liposomal doxorubicin-induced moderate to severe hand-foot syndrome in breast cancer patients: assessment of baseline clinical parameters

Abstract: Background Hand-foot syndrome (HFS) is a side effect of skin related to pegylated liposomal doxorubicin (PLD) application. Moderate to severe hand-foot syndrome (MSHFS) might have a serious impact on patients’ quality of life and treatment. However, information on risk factors for the development of MSHFS is still limited. To analyze the risk factors for PLD-induced MSHFS in breast cancer patients and constructed a logistic regression prediction model. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…Although the above results demonstrated that prophylactic pyridoxine reduced the rate of HFS, many studies have shown that prophylactic pyridoxine is not the only contributing factor [21,22]. In our study, we found that in the absence of pyridoxine prophylaxis, more cycles of PLD chemotherapy (> 3) and low albumin levels were signi cant risk factors for HFS.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Although the above results demonstrated that prophylactic pyridoxine reduced the rate of HFS, many studies have shown that prophylactic pyridoxine is not the only contributing factor [21,22]. In our study, we found that in the absence of pyridoxine prophylaxis, more cycles of PLD chemotherapy (> 3) and low albumin levels were signi cant risk factors for HFS.…”
Section: Discussioncontrasting
confidence: 54%
“…This may be because if a patient has a low albumin level, it can in uence the proliferation of skin cells, resulting in a greater susceptibility to HFS [22]. Referring to baseline albumin-related biomarkers could therefore be bene cial for preventing HFS and making appropriate modi cations to the PLD dosage.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because if a patient has a low albumin level, it can influence the proliferation of skin cells, resulting in a greater susceptibility to HFS. 25 Referring to baseline albumin-related biomarkers could be beneficial for preventing HFS and making appropriate modifications to the PLD dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al [ 25 ] found that BMI is an independent risk factor for moderate to severe HFS, and the two are directly proportional. Patients with high BMI seemed more likely to develop HFS in our study (Table 10 ), although this was statistically non-significant.…”
Section: Discussionmentioning
confidence: 99%